'Finland kills with a pen' – asylum seekers' protest against bureaucratic violence as politics of human rights. Issue 8 (16th November 2020) - Näre, Lena
ABSTRACT: This article contributes to the literature on non-citizens' protests by analysing asylum seekers' claims to right to life as a case of politics of human rights. By analysing asylum seekers' protests as making visible the structural and bureaucratic violence of the state that violates their fundamental human rights, this article offers a reading of non-citizen protests as an engagement in the politics of human rights. Based on ethnographic fieldwork at the Right to Live protest in Finland, I discern the modalities of the injuries experienced by asylum seekers and their critique of the state. Their critique focuses on the bureaucratic violence of rendering asylum seekers illegal and the threat of deportation, as well as the violence of an arbitrary state expressed in legislative changes.